Awareness on Fundamentals of Fixed Prosthodontics among Dental Students in Riyadh Elm University, Saudi Arabia - Alturkmani, Nagham; Alfares, Noor; Albarqi, Shahad; Alshalan, Razan; Aldakheel, Nouf; Alshunaifi, Lamia; Ansari, Shahzeb (International Journal of Health Sciences, 2023)
Purpose: Dentists learn the fundamentals of fixed prosthodontics in dental school and many forms of continuous education. However, there is more to fixed prostheses than the fundamentals, such as the technical aspects, laboratory skills, and keeping up with the current developments of dental materials. This study aims to create awareness on fundamentals of fixed prosthodontics among dental students and dental intern in Riyadh Elm University. Methodology: A descriptive cross-sectional study was done amongst the dental students and dental intern in Riyadh Elm University in Riyadh, Saudi Arabia in 2022. A total of 380 dental students and dental intern were selected randomly. A survey was conducted through online questionnaire composed of 15 multiple-choice questions. Data from the completed questionnaires were analyzed using the SPSS Statistical Software Package (version 25). All statistical analyses were carried out at a significance level of P < 0.05. Results were analyzed and compared using the Chi-square test and frequency test. Results: This cross"‘sectional study showed that most of participants 231 (60.8%) fabricated study models routinely before starting treatment. 244 (64.2%) of participants always used radiographs for abutment tooth evaluation. 276 (72.6%) of participants always used High speed hand piece and 36 198 (52.1%) use Diamond bur during preparation. Also in our study 253 (66.6%) of the participants were using Putty and wash techniques 134 (35.3%) of dental student and dental intern use Condensation cured silicon material for the final impression. A total of 239 (62.9%) of them always used retraction cord before making final impression. In present study the majority of respondents, 133 (35%) always used Silicon and wax material for bite registration. 146 (38.4%) preferred to use only Written prescriptions and 125 (32.9%) used Both written prescriptions and verbal communications. In the end, 224 (58.9%) of respondents disinfect the final impression chemically before pouring it and sending it to lab. Conclusion: The Dental student and dental intern of Riyadh Elm University displayed an acceptable level of knowledge and a level of awareness of fixed prosthodontics practicing. However, to further enhance the proficiency, efforts should be made to encourage the practitioners to be aware of the advances in fixed prosthodontics practice through state-of-the-art continuous education programmers. Unique Contribution to Theory, Policy and Practice: The study's findings could contribute to the theoretical understanding of fixed prosthodontic practices and the knowledge required of dental students and interns. By demonstrating that these students possess an acceptable level of knowledge, the study could support existing theories about dental education and the effectiveness of current curricula.